Characterization of the School Neighborhood Food Environment in Three Mexican Cities. Issue 2 (4th March 2017) - Soltero, Erica G.; Ortiz Hernández, Luis; Jauregui, Edtna; Lévesque, Lucie; Lopez Y Taylor, Juan; Barquera, Simón; Lee, Rebecca E.
ABSTRACT: Food resources in school neighborhoods can negatively influence diet; however, this environment is understudied. This study characterized the school neighborhood food environment in Guadalajara ( n =11), Puerto Vallarta ( n =7), and Mexico City ( n =14). Convenience stores, table-service restaurants, and taco stands were highly available in all three cities. Grocery stores were highly available in Mexico City school neighborhoods, yet less frequently observed in Guadalajara and Puerto Vallarta. Socioeconomic differences in food cart and grocery store availability were observed in Guadalajara and Puerto Vallarta. Policy and intervention strategies are needed to address the saturation of food resources in Mexico school neighborhoods.